Heart–lung vs. double‐lung transplantation for idiopathic pulmonary arterial hypertension. (4th November 2015) - Hill, Charles; Maxwell, Bryan; Boulate, David; Haddad, Francois; Ha, Richard; Afshar, Kamyar; Weill, David; Dhillon, Gundeep S.
Abstract: Patients with idiopathic pulmonary arterial hypertension (IPAH) have improved survival after heart–lung transplantation (HLT) and double‐lung transplantation (DLT). However, the optimal procedure for patients with IPAH undergoing transplantation remains unclear. We hypothesized that critically ill IPAH patients, defined by admission to the intensive care units (ICU), would demonstrate improved survival with HLT vs. DLT. All adult IPAH patients (>18 yr) in the Scientific Registry of Transplant Recipients (SRTR) database, who underwent either HLT or DLT between 1987 and 2012, were included. Baseline characteristics, survival, and adjusted survival were compared between the HLT and DLT groups. Similar analyses were performed for the subgroups as defined by the recipients' hospitalization status. A total of 928 IPAH patients (667 DLT, 261 HLT) were included in this analysis. The HLT recipients were younger, more likely to be admitted to the ICU, and have had their transplant in previous eras. Overall, the adjusted survivals after HLT or DLT were similar. For recipients who were hospitalized in the ICU, DLT was associated with worse outcomes (HR 1.827; 95% CI 1.018–3.279). In IPAH patients, the overall survival after HLT or DLT is comparable. HLT may provide improved outcomes in critically ill IPAH patients admitted to the ICU at time of transplantation.